Molecular phylogenetics of mouse opossums: new findings on the phylogeny of Thylamys (Didelphimorphia, Didelphidae) - Palma, R. Eduardo (2014)
The mouse opossums of the genus Thylamys constitute a group of species mainly adapted to open xeric-like habitats and restricted to the southern portion of South America. We used molecular data (mitochondrial and nuclear sequences) to evaluate the phylogenetic and biogeographical relationships of all currently known living species of the genus, recognizing a new taxon from the middle and high elevations of the Peruvian Andes and evaluating the phylogenetic structuring within T. pallidior and T. elegans, as well as the validity of T. sponsorius, T. cinderella and T. tatei, and the haplogroups recognized within T. pusillus. Our results confirm the monophyly of the genus and that the Caatinga and the Cerrado inhabitants Thylamys karimii and T. velutinus are the most basal species in the radiation of Thylamys. We also calibrated a molecular clock which hypothesized a time of origin of the genus of about 24 My, with most species differentiating in middle and late Miocene and Plio-Pleistocene times of South America.